Wpływ zmiany strategii kartelu OPEC na ceny ropy naftowej - Suder, Jacek (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
The article summarizes recent events related to the crude oil market, regarding particularly the policy of reduction in the commodity supply introduced by the countries of the OPEC cartel and Russia. The author examined the next steps undertaken by member nations of the oil association, which were targeted at an increase in the price of oil and at lowering the level of crude oil reserves in the OECD countries. In addition, the process of creating a shale revolution in the United States was outlined, which led to a great level of independence of this country from the supply of energy resources from other parts of the world. The article is an attempt to introduce a wider topic which is the shale revolution in the USA, and its and impact on the global oil market. It is also a starting point for further considerations regarding possible steps of the OPEC cartel arising after expiration of the current agreement.
The impact on oil prices of the change in OPEC cartel strategy
Keywords: crude oil; OPEC; trade war; the US shale revolution